Analysis of SWOT Application of Marketing Management in Business Developers at PT. Rizki Mandiri Barokah - Amanda Damayanti Nasution; Wahyu Syarvina (Journal of Indonesian Management, 2022)
The purpose of this study is to find the right marketing strategy to be applied in PT. Rizki Mandiri Barokah in Medan city with SWOT analysis. This research is a descriptive study with a qualitative approach. Where non population and sample. This study using key informan to obtain the information needed. The data used are primary data and secondary data. The primary data obtained from interview with the director PT. Sinar Mulya Sejahtera about the company profile and strategy of PT. Rizki Mandiri Barokah Secondary data obtained from target sales and realized sales report. From the analysis conducted known that in recent years, product sales has decreased. The decrease can be happen because the company never knew and never do the analysis about market environment changes, market demand, and low marketing activities. SWOT analysis conducted to determine the strengths, weakness, opportuniteies, and threats in PT. Rizki Mandiri Barokah.